1987
DOI: 10.1126/science.3685979
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Cell Rejection Through Terminal Cell Differentiation

Abstract: Leukemic cells cultured in the presence of various conditioned media differentiate into macrophages. This finding suggested that the maintenance of undifferentiated state and self-renewal in vivo may be related to the inability of the host to generate an appropriate level of differentiation factor (DF). Evidence for this hypothesis was derived from experiments in vitro and in vivo with myeloid leukemia of rat. The following results were obtained: (i) in vitro, the percentage of cell differentiation at a fixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…By and large, most of the differentiation agents studied to date have demonstrated significantly less toxicity as compared to standard cancer treatments. Indeed, differentiation therapy is an approach to the treatment of advanced or aggressive malignancies and showed significant efficacy in the treatment of many types of cancer (Jimenez and Yunis, 1987). We have recently demonstrated that AE, a hydroxyanthraquinonic compound present mostly in A. barbadensis Miller leaves and in Rheum palmatum L. roots, possesses a differentiative potential on melanoma cells (Tabolacci et al, 2010a).…”
Section: Discussionmentioning
confidence: 99%
“…By and large, most of the differentiation agents studied to date have demonstrated significantly less toxicity as compared to standard cancer treatments. Indeed, differentiation therapy is an approach to the treatment of advanced or aggressive malignancies and showed significant efficacy in the treatment of many types of cancer (Jimenez and Yunis, 1987). We have recently demonstrated that AE, a hydroxyanthraquinonic compound present mostly in A. barbadensis Miller leaves and in Rheum palmatum L. roots, possesses a differentiative potential on melanoma cells (Tabolacci et al, 2010a).…”
Section: Discussionmentioning
confidence: 99%
“…Both of these processes yield the expansion of a malignant cell population, characterized by a high proliferative potential and a low differentiation state. In this light, the pathological features of transformed cells can be reversed by pharmacological treatments capable of restoring a differentiated phenotype, rather than inducing cytotoxicity, in transformed cells (Sachs, 1978;Fisher and Grant, 1985;Jiminez and Yunis, 1987): this emerging strategy aims at tumor reversion using compounds that ''force'' tumor cells to re-enter the terminal differentiation program through a process termed ''differentiation therapy.'' Retinoic acid is the prototype agent of this kind, a classical morphogen in embryo development and an active inducer of differentiation, first fractionated from anticancer remedies in traditional chinese medicine, now widely used to treat leukemia of several types.…”
Section: Toward a Differentiating Anticancer Therapymentioning
confidence: 99%
“…Loss of the ability to undergo normal cell differentiation is one of the important mechanisms of tumorigenesis [40,41]; cell differentiation, especially terminal cell differentiation, often becomes aberrant in cancer [42,43]. Efforts are being made to develop anticancer therapeutic interventions to restore terminal differentiation in cancer cells [43–46].…”
Section: Function Of 15-lox-1 In Normal Cellsmentioning
confidence: 99%